2013
DOI: 10.1002/chem.201300793
|View full text |Cite
|
Sign up to set email alerts
|

Host–Guest Complexation of [60]Fullerenes and Porphyrins Enabled by “Click Chemistry”

Abstract: Herein the synthesis, characterization, and organization of a first-generation dendritic fulleropyrrolidine bearing two pending porphyrins are reported. Both the dendron and the fullerene derivatives were synthesized by Cu(I) -catalyzed alkyne-azide cycloaddition (CuAAC). The electron-donor-acceptor conjugate possesses a shape that allows the formation of supramolecular complexes by encapsulation of C60 within the jaws of the two porphyrins of another molecule. The interactions between the two photoactive unit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(34 citation statements)
references
References 72 publications
0
15
0
Order By: Relevance
“…This arises as a consequence of strong πstacking interactions with other small molecules in aqueous solution [5]. The effect of complexation had mainly been investigated in terms of the formation of supramolecular C60 fullerene-ligand ordered structures [6,7], host-guest phenomena [8,9] or C60 fullerene binding with micelles [10,11]. However, during the past five years the complexation of pristine C60 fullerene with small drug molecules in aqueous solution has become a major focus of scientific investigation.…”
Section: Introductionmentioning
confidence: 99%
“…This arises as a consequence of strong πstacking interactions with other small molecules in aqueous solution [5]. The effect of complexation had mainly been investigated in terms of the formation of supramolecular C60 fullerene-ligand ordered structures [6,7], host-guest phenomena [8,9] or C60 fullerene binding with micelles [10,11]. However, during the past five years the complexation of pristine C60 fullerene with small drug molecules in aqueous solution has become a major focus of scientific investigation.…”
Section: Introductionmentioning
confidence: 99%
“…The rotaxanes studied in this work were prepared according to Scheme 1, using a recently reported tandem active metal templated copper alkyne–azide cyclization (CuAAC) reaction, in which zinc and copper promote the formation of dumbbells within a phenanthroline-strapped porphyrin 39. Azide stopper 2 ,40 fullerene derivative 3 ,41 and phenanthroline-strapped porphyrin 4Zn ,42,43 were synthesized according to reported methods. Compounds 3 , 4 , and 4Zn also served as references for the photophysical studies.…”
Section: Resultsmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9][10][11][12][13][14] Their photophysical properties have been investigated in details, revealing that the deactivation scenario can be affectedb ys everal parameters, such as the polarity of the solvent [15][16][17][18][19][20][21][22][23] or the interchromophoric distance. [29,[33][34][35][36][37][38][39][40][41][42][43] For example, we have reported the synthesis of the hybrid system fullerene-porphyrin-fullerene( F-P-F,s ee the structure below).T his compoundwas prepared by the reactiono faC 60 derivative bearing an azide functional group [34,35] with aZ n II -porphyrin bearing two terminal alkyne groupsu nder the copper-mediated Huisgen 1,3-dipolar cycloaddition conditions. [29,[33][34][35][36][37][38][39]…”
Section: Introductionmentioning
confidence: 99%
“…[24][25][26][27][28][29][30][31][32] As part of this research, it has been shown that the fullerene-porphyrin conjugation can be convenientlya chieved by using copper-catalyzed alkyne-azide cycloaddition (CuAAC) reactions. [29,[33][34][35][36][37][38][39][40][41][42][43] For example, we have reported the synthesis of the hybrid system fullerene-porphyrin-fullerene( F-P-F,s ee the structure below).T his compoundwas prepared by the reactiono faC 60 derivative bearing an azide functional group [34,35] with aZ n II -porphyrin bearing two terminal alkyne groupsu nder the copper-mediated Huisgen 1,3-dipolar cycloaddition conditions. [44][45][46][47][48] Detailed photophysical studies revealed strong excited-state interactions between the different components in the conjugate F-P-F. [34,49] In particular,a ne fficient photoinduced electron transfer from both fullerenea nd porphyrin triplet levels has been evidenced in benzonitrile.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation